THE PROBLEM OF SEMANTICS IN PROPER AND COMMON NAMES - Olimova Xurshida Vaydillayevna; Feruza Mamashukurova (Innovate Conferences, 2025)
It is well known that the issue of the relationship between a name and a concept has not yet been resolved. This situation repeatedly brings the question of the relationship between proper and common nouns back to the agenda. The article investigates the relationship between proper and common nouns and analyzes the semantic features specific to proper nouns.
Keywords: Proper noun, common noun, denotatum, signifikat, connotation, semantics, concept.